1998
DOI: 10.1063/1.122708
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast phase dynamics of coherent carriers in GaAs

Abstract: Ultrafast phase dynamics of free-induction decay for carriers in bulk GaAs is studied with differential-phase spectroscopy. The instantaneous phase shifts of the free-induction decay with respect to the excitation pulses are extracted from simultaneously recorded laser pulse autocorrelation and free-induction decay in GaAs. Ultrafast phase dynamics during and immediately after the femtosecond pulse excitation are numerically evaluated with optical Bloch equations using pump pulse and semiconductor exciton para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…The optical Bloch equations have been used by others to simulate the coherent field-matter interaction, including the time-resolved photoemission of metallic systems 34,51 and the free-induction decay of semiconductors. 38 In this study, the formalism is adapted to describe the dephasing of the coherently driven plasma oscillation of single Ag nanoparticles.…”
Section: Theory and Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…The optical Bloch equations have been used by others to simulate the coherent field-matter interaction, including the time-resolved photoemission of metallic systems 34,51 and the free-induction decay of semiconductors. 38 In this study, the formalism is adapted to describe the dephasing of the coherently driven plasma oscillation of single Ag nanoparticles.…”
Section: Theory and Backgroundmentioning
confidence: 99%
“…This technique has been used in studies of the ultrafast dynamics of metallic films, 34,35 structured metal particle arrays, 13,36,37 and bulk semiconductors. 38 In general, however, most of the experimental investigations in this area have examined ensembles of particles, thereby averaging over a distribution of particle sizes, adding an inhomogeneous contribution to the measured response. Because the electron-phonon dynamics of nanoparticles are strongly affected by their shape (and perhaps size), 8,11,[39][40][41] the dephasing and the relaxation times obtained in these studies should be regarded as a lower limit; the contribution of (structural) inhomogeneity to the dephasing cannot be separated from the homogeneous contribution by pump-probe nonlinear spectroscopies.…”
Section: Introductionmentioning
confidence: 99%
“…Here is the intraband momentum scattering time, 18 and and are the real and imaginary parts, respectively, of the modified electric field envelope 6 . The dephasing rate is denoted by and is the detuning.…”
Section: Andmentioning
confidence: 99%
“…13,17 We note that previous studies in which the frequency modulated coherent polarization has been shown to play an important role addressed different physical effects. 6…”
mentioning
confidence: 99%
“…which currently can be experimentally generated accurately by controlling the relative distance between the two paths in the Michelson interferometer [36]. Here, ω L denotes the oscillatory frequency of the laser fields and c.c stands for the complex conjugation of the driving fields.…”
Section: Physical Model and Single-photon Transportmentioning
confidence: 99%